Clinical profile of scrub typhus in relation with malaria and dengue seasonal outbreak from semi desert area of Rajasthan, India - Gupta, Virendra Kumar; Agrawal, Prashant; Gupta, Raj Kumar; Sharma, Ram Babu; Bhatnagar, Jitendra Prashad (International Journal of Contemporary Pediatrics, 2016)
Background: Scrub typhus is a zoonotic disease caused by rickettsial bacteria Orientia tsutsugamushi. The disease is endemic in many parts of India. Recent appearance of cases from semi desert district of Rajasthan is highly concerning. The aim and objectives of the study was to present epidemiological demographic profile and distribution, clinical manifestation, laboratory Findings and treatment outcomes of scrub typhus in children. Methods: A hospital based cross sectional observational stud, ten cases were included having positive IgM antibody against Orientia tsutsugamushi. Their clinical details were taken along with complete physical examination. Laboratory testing included complete blood count, liver function tests, renal function tests, urine analysis, blood & urine cultures. Results: Of ten children, mean age were 9.7±2.40 years, male, female ratio 1.5, mean duration of hospital stay 7±2.35 days. Fever (100%) was most common presenting symptom and mean duration was 6.8±2.78 days. Other features were tachycardia (80%), tachypnoea (70%), heptoslenomegaly (70%), swelling (60%), vomiting (60%), abdominal pain (40%), rashes (40%), bleeding (30%) and seizures (20%). Thrombocytopenia (80%) and mild elevated liver enzymes were present in most of the cases. Eschar was present only in two (20%) cases. Nine cases were successfully treated with doxycycline and one mortality due to CNS involvement. Conclusions: Our study emphasizes that pediatric scrub typhus should be suspected when patient presents with high grade fever with heptoslenomegaly with or without eschar mark along with thrombocytopenia and elevated liver enzymes. Early diagnosis could reduce the morbidity and mortality. Drugs useful are Doxycycline, Azithromycin or Chloramphenicol.